A Contribution to the Knowledge of Tropical Wet Evergreen Forests-the Sholas of Papanasam Hills in Madras State - Rajasingh, G. J. (Indian Forester, 1961)
The Papanasam Hills of the Western Ghats, in Tirunelveli North Division of Madras State, contain some of the best virgin evergreen forests which can form an interesting subject for study. The sholas (as they are locally called) range from 2,000 to 4,500 feet where the rainfall varies from 120 to 200 inches. Within the general limits of the evergreen zone, climatic climaxes and edaphic variations can be recognised with reference to characterestic species and nature of growth. The ecological status of a pure reed climax found in the interior regions is also discussed. The two species peculiar to the hills are Cluta travancorica and Balanocarpus utilis a short account of which is also given.